Rare Lipomatous Tumors with Osseous and/or Chondroid Differentiation in the Oral Cavity Report of Two Cases and Review of the Literature - Kayo Kuyama; Sisilia Fusi Fifita; Masamichi Komiya; Yan Sun; Yoshiaki Akimoto; Hirotsugu Yamamoto (International Journal of Dentistry)
The purpose of this study was to determine the clinicopathological and immunohistochemical features of lipoma/fibrolipoma with rare occasions as osseous and/or chondroid differentiation in the oral cavity. Two cases of the tumors, who presented with a painless, relatively hard mass on the oral mucosa, were studied. These were consisted of a well-circumscribed mass of fatty tissue with chondroid and significant fibrous component intermixed with the lobules of fat cells with chondroid and woven bone component, respectively. Immunohistochemical study revealed that peripheral spindle cells around chondroid tissue stained diffusely for S-100 𝛼 & 𝛽 and Sox-9, though peripheral spindle cells around osteoid tissue only stained for RUNX-2. According to review of the literature, lipoma/fibrolipoma with osseous and/or chondroid differentiation was 18 cases. Also fibrolipoma with osseous and chondroid differentiation is the first to be reported here. These results indicated that the cartilage/bone is produced by differentiation of undifferentiated mesenchymal cells of stroma.